Direct immunofluorescence test for Campylobacter fetus subsp. venerealis in breeding bulls of Costa Rica - Navarro, Leonel (2025)
Bovine genital campylobacteriosis (BGC) is a venereal infectious disease caused by a Gram-negative bacillus Campylobacter fetus subspecies venerealis (Cfv) that impairs the reproductive efficiency in cattle herds. The clinical diagnosis of BGC is based on low fertility in the breeding herd; however, laboratory confirmation is required. Although there is data on the disease being distributed worldwide, particularly in cattle herds where natural mating is the primary breeding system, data from Costa Rica is unavailable. This study aimed to detect the presence of Campylobacter fetus subsp. venerealis (Cfv) in scrapings collected from the preputial mucosa of breeding bulls allocated in the North Huetar and North Pacific regions of Costa Rica using direct immunofluorescence (DIF). There was no data regarding reproductive problems on any of the 157 participating farms. Scrapings of the preputial mucosa were collected using a plastic rod-type aspirator-scraper introduced into the preputial cavity, stored in 1% phosphate-buffered formalin, and subsequently analyzed by DIF. All the bulls tested yielded negative for the pathogen. The possible causes related to this result are discussed in this article.